2007
DOI: 10.1111/j.1365-3040.2007.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐mediated changes in hydraulic conductivity of deep tree roots accessed via caves

Abstract: Although deep roots can contribute substantially to wholetree water use, little is known about deep root functioning because of limited access for in situ measurements. We used a cave system on the Edwards Plateau of central Texas to investigate the physiology of water transport in roots at 18-20 m depth for two common tree species, Quercus fusiformis and Bumelia lanuginosa. Using sap flow and water potential measurements on deep roots, we found that calculated root hydraulic conductivity (RHC) fluctuated diur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 62 publications
5
71
0
Order By: Relevance
“…Aquaporins are a family of transmembrane proteins considered to be largely responsible for the high permeability to water exhibited by plasma membranes. The regulation of R h by aquaporins is now well documented in roots (Martre et al, 2001;McElrone et al, 2007;Vandeleur et al, 2009), and oxidative gating of aquaporins has been reported to reduce hydraulic conductivity by 90% in cells of the giant algae Chara (Henzler et al, 2004). The results of previous work suggest that aquaporins play an important role in the regulation of water movement during the development of flowers, seeds, and fruits (Maurel et al, 1995;Gao et al, 1999;Picaud et al, 2003;Shiota et al, 2006;Zhou et al, 2007).…”
mentioning
confidence: 87%
“…Aquaporins are a family of transmembrane proteins considered to be largely responsible for the high permeability to water exhibited by plasma membranes. The regulation of R h by aquaporins is now well documented in roots (Martre et al, 2001;McElrone et al, 2007;Vandeleur et al, 2009), and oxidative gating of aquaporins has been reported to reduce hydraulic conductivity by 90% in cells of the giant algae Chara (Henzler et al, 2004). The results of previous work suggest that aquaporins play an important role in the regulation of water movement during the development of flowers, seeds, and fruits (Maurel et al, 1995;Gao et al, 1999;Picaud et al, 2003;Shiota et al, 2006;Zhou et al, 2007).…”
mentioning
confidence: 87%
“…Plants growing in tiny, shallow soils and rocky habitats tend to allocate more resources to roots to maintain and physically support the ecosystem. However, dominant canopy tree species in karst forests have low net photosynthetic rate and low light photosynthetic productivity (Yang, 2011), but changes of hydraulic conductivity of deep tree roots may help the trees maintain the use of reliable water resources from depth (McElrone et al, 2007). Such ecophysiological evidences imply that karst forests have lower growth rate and lower biomass and productivity, but in such a shallow-water lacking environment more roots are developed to elevate deeper groundwater.…”
Section: Comparison With Subtropical Forestsmentioning
confidence: 99%
“…Specifically, plants spent their energy on active transport of water when they suffered from the extreme environment, e.g. the storage water in plants was insufficient to meet their metabolic activities, or plants urgently needed to lift water from groundwater into shallow soils via plant stems to absorb minerals (McElrone et al 2007;Prieto et al 2012;Johnson et al 2014). Within the HL process, it may be not enough water potential difference to lift water from deep soil layers or groundwater to shallow soil layers due to transpiration shutoff at night (Prieto et al 2012).…”
Section: Fluctuations In Fine Roots Distribution Water and Mineral Rmentioning
confidence: 99%